Low-molecular-weight heparin and recurrent placenta-mediated pregnancy complications: a meta-analysis of individual patient data from randomised controlled trials. Issue 10060 (26th November 2016) - Rodger, Marc A; Gris, Jean-Christophe; de Vries, Johanna I P; Martinelli, Ida; Rey, Évelyne; Schleussner, Ekkehard; Middeldorp, Saskia; Kaaja, Risto; Langlois, Nicole J; Ramsay, Timothy; Mallick, Ranjeeta; Bates, Shannon M; et al.
Summary: Background: Placenta-mediated pregnancy complications include pre-eclampsia, late pregnancy loss, placental abruption, and birth of a small-for-gestational-age (SGA) neonate. These complications are leading causes of maternal, fetal, and neonatal morbidity and mortality in high-income countries. Affected women are at high risk of recurrence in subsequent pregnancies; however, effective strategies to prevent recurrence are absent. Findings from our previous study-level meta-analysis suggested that low-molecular-weight heparin reduced the risk of recurrent placenta-mediated pregnancy complications. However, we identified significant heterogeneity in the results, possibly due to trial design or inclusion criteria. To identify which patients benefit from, and which outcomes are prevented by, low-molecular-weight heparin, we did an individual patient data meta-analysis. Methods: We did a systematic review in May, 2013, which identified eight eligible randomised trials done between 2000 and 2013 of low-molecular-weight heparin to prevent recurrent placenta-mediated pregnancy complications. We excluded studies on the basis of the wrong population, the study being ongoing, inability to confirm eligibility of participants, intervention stopped too early, and no response from the principal investigator. We requested individual patient data from the study authors for eligible women (women pregnant at the time of the study with a history of previous pregnancy that had been complicated by one or more of the following: pre-eclampsia, placental abruption, birth of an SGA neonate [<10th percentile], pregnancy loss after 16 weeks' gestation, or two losses after 12 weeks' gestation) and recoded, combined, and analysed the data for our meta-analysis. The primary outcome was a composite of early-onset (<34 weeks) or severe pre-eclampsia, birth of an SGA neonate (<5th percentile), late pregnancy loss (≥20 weeks' gestation), or placental abruption leading to delivery, assessed on an intention-to-treat basis. We assessed risk of bias with the Cochrane Risk of Bias tool. This study is registered with PROSPERO, number CRD42013006249. Findings: We analysed data from 963 eligible women in eight trials: 480 randomly assigned to low-molecular-weight heparin and 483 randomly assigned to no low-molecular-weight heparin. Overall, the risk of bias was not substantial enough to affect decisions regarding trial inclusion. Participants were mostly white (795/905; 88%) with a mean age of 30·9 years (SD 5·0) and 403/963 (42%) had thrombophilia. In the primary analysis, low-molecular-weight heparin did not significantly reduce the risk of recurrent placenta-mediated pregnancy complications (low-molecular-weight heparin 62/444 [14%] versus no low-molecular-weight heparin 95/443 (22%) absolute difference −8%, 95% CI −17·3 to 1·4, p=0·09; relative risk 0·64, 95% CI 0·36–1·11, p=0·11). We noted significant heterogeneity between single-centre and multicentre trials. In subgroup analyses, low-molecular-weight heparin in multicentre trials reduced the primary outcome in women with previous abruption (p=0·006) but not in any of the other subgroups of previous complications. Interpretation: Low-molecular-weight heparin does not seem to reduce the risk of recurrent placenta-mediated pregnancy complications in at-risk women. However, some decreases in event rates might have been too small for the power of our study to explore. Funding: Canadian Institutes of Health Research.